The Jurisprudence of the European Court of Human Rights as an Instrument to counter the Rule of Law backsliding en National Legal Systems (Some Doctrinal Reflections) - Yuliia Reminska (Estudios de Deusto, 2023)
The interaction between states and European interstate organizations has taken on a new dimension: through purely domestic doctrine the Rule of Law idea becomes standardised using European informal law-making. The current paper analyses how the European Court of Human Rights can modernise and develop the content of the Rule of Law. This paper offers two main contributions to theoretical legal thought. First, it pinpoints the necessity to conceptualise the meaning and content of the Rule of Law via the instruments of judicial interpretation. Being incorporated in every article of the European Convention, the Rule of Law is interpreted by the Strasbourg Court with the aid of a “living instrument approach”. Second, this article categorises the difference between two main structural levels of the Rule of Law: its principles and their requirements. This allowed the author to build a Rule of Law anti-backsliding “reference system” that is designed in a way that is directly based on judgments rendered by the Court. It is argued that this may be useful for state legal systems as through its jurisprudence, the Court has developed a robust framework for assessing whether a member state violates the Rule of Law standards. The suggested framework has been used to hold member states accountable for their actions and to prevent any backsliding of the Rule of Law in Europe.